KEDUDUKAN ANAK DALAM ALQURAN (Suatu Pendekatan Pendidikan Islam) - Saat, Sulaiman (Inspiratif Pendidikan, 2018)
Abstract: This paper departs from the main problem of how the position of children according to the concept of the Qur'an by making an approach from the eyes of Islamic education. The Qur'an is a timeless guide in every human activity, including education. The Qur'an has given clues about children's education. Children are the most important asset, capital, investment of every family that must be maintained, nurtured, cared for, educated. The Qur'an has given guidance to it. In the Qur'an many verses are found related to education, both the purpose, method, and the content of education itself.